Probiotic Microorganisms in Inflammatory Bowel Diseases: Live Biotherapeutics as Food - Emanuelle Natalee Santos; Karina Teixeira Magalhães-Guedes; Fernando Elias de Melo Borges; Danton Diego Ferreira; Daniele Ferreira da Silva; Pietro Carlos Gonçalves Conceição; Ana Katerine de Carvalho Lima; Lucas Guimarães Cardoso; Marcelo Andrés Umsza-Guez; Cíntia Lacerda Ramos (Foods)
(1) Background: Inflammatory bowel diseases (IBDs) are characterized by chronic and complex inflammatory processes of the digestive tract that evolve with frequent relapses and manifest at any age; they predominantly affect young individuals. Diet plays a direct role in maintaining the gut mucosal integrity and immune function. Regarding the diet, the administration of probiotics stands out. The use of probiotics for IBD treatment has shown promising effects on consumers’ quality of life. (2) Methods: This study aimed to conduct a literature review on the effects of probiotic and smart probiotic ingestion on IBD and analyze the available literature based on the searched keywords using boxplot diagrams to search for scientific data in the online literature published up to October 2024. (3) Results: Google Scholar (containing ~6 × 106 articles) and Science Direct (containing ~5 × 106 articles) were the databases with the highest number of articles for the keywords used in the study. When analyzing the content of the articles, although probiotic microorganisms are currently not part of the standard treatment protocol for IBD, these live biotherapeutics have proven to be an effective treatment option, considering the adverse effects of conventional therapies. Furthermore, the development of genetically engineered probiotics or smart probiotics is a promising treatment for IBD. (4) Conclusions: Probiotics and smart probiotics could represent the future of nutritional medicine in IBD care, allowing patients to be treated in a more natural, safe, effective, and nutritious way. However, although many studies have demonstrated the potential of this biotherapy, clinical trials standardizing dosage and strains are still necessary.